Kepemimpinan Melayu dalam Peribahasa - Elmustian Elmustian; Hermandra Hermandra; Yusron Hadi Falah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to examine the values of Malay leadership reflected in proverbs, particularly the expression “a just ruler is obeyed, an unjust ruler is opposed.” In Malay culture, leadership is not merely understood as formal authority but also as a moral responsibility grounded in tradition, religion, and wisdom. This research employs a descriptive qualitative method using a literature review approach by collecting data from journals, articles, and other relevant academic sources. The findings reveal that Malay proverbs contain essential leadership values such as justice, trustworthiness, reciprocal relationships between leaders and the people, rejection of tyranny, and the importance of moral and ethical conduct. Furthermore, these proverbs reflect social and cultural values emphasizing consensus and harmony in society. Therefore, Malay proverbs function not only as linguistic expressions but also as guidelines for shaping ideal leadership character. These values remain relevant in modern contexts as a foundation for fostering just, wise, and responsible leadership